Winds and windstorms in northern Europe and Finland - Laurila, Terhi K. (Ilmatieteen laitos, 2022)
Strong winds can cause large impacts and damage to society. Many sectors, such as wind energy, forestry and insurance, are highly affected by winds. Thus, preparedness and adaptation to winds and windstorms is essential in both weather (days) and climate (decades) time scales. The aim of this thesis is to better understand the near surface mean and extreme wind climate in northern Europe and Finland and the role of extratropical cyclones in contributing to the extreme winds. This thesis investigated the main characteristics of wind and windstorm climate in northern Europe and Finland over a 40-year period. The wind and windstorm climate was found to have large inter-annual and decadal variability and no significant linear trends. The well-known seasonal cycle was detected: winds in northern Europe are up to 30 % stronger in winter than in summer and while there are on average 5–6 windstorms per month in winter in northern Europe there are none in summer months. A more surprising result was that the number of all extratropical cyclones does not vary between seasons. Windstorms were found to be the most frequent over the Barents Sea whereas weaker extratropical cyclones occur over the land areas in northern Europe. The development and structure of strong winds in windstorms in northern Europe and Finland were examined. The results show that the strongest wind gusts associated with windstorms shift and extend from the warm sector to behind the cold front during the evolution. The cold-season (Oct–Mar) windstorms are overall stronger and spatially larger than warm-season (Apr–Sep) windstorms. For example, the central pressure is on average 9 hPa deeper and the maximum wind gust 2 ms-1 stronger in cold-season windstorms than in warm-season windstorms. Analysing a case study of storm Mauri, a damaging windstorm in Finland in September 1982, shows that an individual windstorm development can vary largely from the climate’s general concept. The case study also found that during storm Mauri the wind speeds over land ...